Інноваційна система ЕС: еволюція і напрями розвитку в сучаних умовах - Хаірова, Е.А. (Культура народов Причерноморья, 2013)
Стаття присвячена дослідженню еволюції інноваційної системи ЄС з початку офіційного
об’єднаннякраїн Європи для єдиної регіональної інтеграції. Розглянуто причини створення
наднаціональної системи ЄС та особливості проведення єдиної інноваційної політики. Досліджено
основні заходи ЄС відносно проведення аналізу та оцінки про стан інноваційної діяльності в країнах-
членах. Розглянуті основними пріоритетними напрямами інноваційної діяльності країн ЄС. Стать япосвящен аисследованию эволюции инновационной системы ЕС с начала
официального объединения стран Европы для единой региональной интеграции. Рассмотрены причины
создания наднациональной системы ЕС и особенности проведения единой инновационной политики.
Исследованы основныемеры ЕС в отношении и проведения анализа и оценки о состоянии и
инновационной деятельности в странах-членах. The article is devoted to the evolution of the innovation system in the EU since the beginning of the
official Union of countries in Europe for a common regional integration. The reasons of creation of a
supranational system of the EU and especially for a unified innovation policy. The main EU measures for the
analysis and assessment on the state of innovation activities in the member countries. Considered the main
priority directions of innovation activity of the EU countries.Describes the main aspects of the implementation of
the Lisbon strategy, which embarked on the creation and fast development of a competitive innovative economy.
We analyzed the results of the most authoritative international rating of innovative activity of the countries of the
European innovation scoreboard, which provides a comparative assessment of innovative activities in the
member States of the EU - 27, as well as the USA and Japan. We consider the direction of implementation of a
single supranational innovation policy that relate to enhance regional and innovative cooperation. In particular,
this led to the development of innovation cooperation among regional economic integration organizations.
Investigated the significance of protection of intellectual EU countries.